RI 7707 Effect Of Fuel Front-End And Midrange Volatility On Automobile Emissions - B. H. Eccleston (The National Institute for Occupational Safety and Health (NIOSH), 1972)
Experimental work is reported showing the effects of gasoline characteristics on auto emissions. Fuel volatility is shown to influence evaporative losses, with the higher losses associated with higher volatility. Fuel front-end olefin is shown to contribute significantly to reactivity of emissions. Large vehicle-to-vehicle differences were found. The study was conducted by the Bureau of Mines at its Bartlesville Energy Research Center in cooperation with the Coordinating Research Council Air Pollution Research Advisory Committee. The work was done using 15 1968-70 model autos and eight fuels were tested at ambients ranging from 20° to 95° F. Data on emissions from each vehicle-fuel-temperature combination are presented. Also included are calculated photochemical reactivity data and the distribution of hydrocarbon and nitrogen oxides during the test cycle.